Abundance of Epiphyas postvittana (Walker, 1863) in forestry nurseries of São Miguel Island (Azores, Portugal) (Lepidoptera: Tortricidae) - L. Oliveira; V. Vieira; A. O. Soares; I. Borges; P. Arruda; J. Tavares (SHILAP)
Epiphyas postvittana (Walker, 1863) is an invasive polyphagous pest for the Azores and its bioecology and the potential natural enemies were unknown. We evaluated the temporal profile of this species larval abundance and the number of males captured in sex pheromone traps, hypothesizing that both profiles were similar. The study was carried out on seven endemic host plants and one native species grown in two forest nurseries (Furnas and Nordeste) in São Miguel Island over two years from 2018 to 2019. A total of 827 plants attacked by E. postvittana were observed in Furnas nursery (2018: 503, 2019: 324) and 1227 in the Nordeste (2018: 649, 2019: 578), including the presence of 525 larvae distributed by the Furnas (2018: 178, 2019: 79) and from the Nordeste (2018: 131, 2019: 137). In 2019, the average weekly number of males captured in the sex pheromone traps (total 31 weeks) were higher in Furnas (mean ± SE: 9.68 ± 1.982) than in Nordeste (3.33 ± 0.651). In synthesis, (i) the population density varied throughout the year and as a function of the host plant species in production; (ii) the abundance profile of larval and adults suggests has at least three to four generations per year and that adults are active year-round, experiencing some delayed development during the winter; (iii) a low larval density does not represent very serious damage to Azorean endemic plants, but is reflected in the population density of its natural enemies; (iv) some biological control agents are present in the field, parasitizing the larvae (i.e., Braconidae species of Meteorus ictericus (Nees, 1811) and Microgaster opheltes Nixon, 1968); (v) finally, the knowledge of the population dynamics and its natural enemies needs further and long-term study.